Motivation and academic performance in the area of mathematics in primary students - Albújar Caile, Karin Vanessa (2014)
The purpose of present research is to establish the relationship between motivation and the performance academic of third grade students of the School N° 11024 “José Quiñones Gonzales”, Chiclayo District, Chiclayo Province, Lambayeque Region. 2014. This study corresponds to the type of descriptive no experimental research Correlational because it allows us to demonstrate the relationship or correlation among the variable of study. The statistical data that support the present investigation were obtained processing the scores of the application of the motivation questionnaire and recording notes for academic performance in the area of Mathematics to the students of grade third of school above mentioned. The results of this investigation demonstrate that significant relationship exists with a p<0.05 between motivation and academic performance of the students of the School N° 11024 “José Quiñones Gonzales”.